Evaluación de parámetros productivos con bases en el aprovechamiento de pastos naturales en el sistema de engorde de bovinos machos de Cotopaxi. - Tayupanta Toapanta, Alex Dario (2021)
The present investigation was carried out in the Potrerillos sector which is located in the Cotopaxi province, Latacunga canton, Belisario Quevedo parish and whose geographical location is 0 ° 58'31.773 ”S south latitude and 78 ° 33´2.514” W longitude west at an altitude of 3202 meters above sea level, where the soil and pasture component for fattening beef cattle was determined taking into account that in pastures and soil an evaluation of the interaction of the availability of nutrients that affect the efficiency production in relation to feeding, in relation to the productive parameters of the animals during the mineral interaction, it was evaluated by weighing the animals, the BUN was determined before and after mineral correction by means of a laboratory and finally a schedule was established of annual fertilization through environmental characterization in order to maintain and improve soil-pasture management. A methodology of direct observation and experimental work was used, where the situation in which the soil-pasture and male bovines were found was verified, we proceeded to take samples of the pastures and soil of the different pastures that grazed them to send Analyze in the laboratory, then 20 cattle were registered with the help of a record sheet noting the numbers of the earrings, which were taken fortnightly. After having obtained the results of the analysis of both pastures and soils, the necessary minerals were verified and later the fertilization of the soils was carried out, in addition, the BUN was determined by means of a laboratory before and after fertilization. Obtaining as results a daily weight gain of 1 ± 0.04 and at the end of theinvestigation the gain of 27 ± 1.04 kg was determined